Transforming Language Learning: How Web-Based Storytelling Enhances Motivation, Creativity, and Language Proficiency - Abhipriya Roy (Scientia Publica Media, 2025)
Digital storytelling thus emerges as a meaningful learner-centred approach that enhances both academic achievement and holistic learning. It equips students with creativity, collaboration, critical thinking, and digital fluency to prepare them for a lifelong learning experience in an increasingly digital world. Digital platforms are strengthening narrative, a powerful literacy tool, extending its reach beyond traditional literature and promoting multidisciplinary learning experiences. This study looked at the pedagogical impact of online storytelling in English-medium schools, focusing on motivation, creativity, and language skills of students. A quasi-experimental mixed method was used in Bangalore, India, with 200 students from four ICSE schools. An experimental group (n = 100) took part in a six-week project of digital storytelling using multimedia tools, while a control group (n = 100) took part in a traditional text-based learning programme. Quantitative data were collected through pre- and post-tests to assess reading, writing, listening, and language skills, as well as a standardised motivation questionnaire. Qualitative insights were derived from semi-structured interviews, teacher observations, and student reflection sheets. The findings showed that the experimental group demonstrated statistically significant improvements in language skills (p<.05), with particularly significant increases in writing and language proficiency. Motivation scores also showed a higher level of engagement, perseverance, and intrinsic motivation in students who used digital storytelling. Additional qualitative data have confirmed that digital storytelling promotes creativity, collaboration, and autonomy of learners, while offering authentic opportunities for interaction with audiences and self-expression. Digital narratives develop 21st-century skills such as digital fluency, creativity, and critical thinking.